2018
DOI: 10.1007/s13592-018-0569-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Lactobacillus bacteria found in the gastrointestinal tract of the dwarf honey bee, Apis florea Fabricius, 1973 (Hymenoptera: Apidae)

Abstract: Recent research in bacteria-insect symbiosis has shown that lactic acid bacteria (LAB) establish symbiotic relationships with several Apis species. The current study was carried out to isolate and identify Lactobacillus bacteria housed in the gastrointestinal tract of the Asian dwarf honey bee (Apis florea), which is distributed in different regions of Iran. The current study was performed using 100 Gram-stained isolates, which were tested for catalase activity. Bacterial universal primers were used to amplify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
0
13
0
2
Order By: Relevance
“…Lactiplantibacillus plantarum [formerly Lactobacillus plantarum (Zheng et al ., 2020)] is included among those nomadic LAB (Duar et al ., 2017) and is known for its significant intraspecific versatility (Molenaar et al ., 2005; Siezen et al ., 2010; Martino et al ., 2016; Cen et al ., 2020). L. plantarum is frequently isolated from fresh and fermented plant, meat and dairy foods and is an inhabitant of the gastrointestinal and vaginal tracts of humans and animals (Delgado et al ., 2005; Aquilanti et al ., 2007; Di Cagno et al ., 2008; Yang et al ., 2010; Ciocia et al ., 2013; Jose et al ., 2015; Zago et al ., 2017; Parichehreh et al ., 2018; Barache et al ., 2020). This species is frequently required for or is involved in the production of numerous fermented foods (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Lactiplantibacillus plantarum [formerly Lactobacillus plantarum (Zheng et al ., 2020)] is included among those nomadic LAB (Duar et al ., 2017) and is known for its significant intraspecific versatility (Molenaar et al ., 2005; Siezen et al ., 2010; Martino et al ., 2016; Cen et al ., 2020). L. plantarum is frequently isolated from fresh and fermented plant, meat and dairy foods and is an inhabitant of the gastrointestinal and vaginal tracts of humans and animals (Delgado et al ., 2005; Aquilanti et al ., 2007; Di Cagno et al ., 2008; Yang et al ., 2010; Ciocia et al ., 2013; Jose et al ., 2015; Zago et al ., 2017; Parichehreh et al ., 2018; Barache et al ., 2020). This species is frequently required for or is involved in the production of numerous fermented foods (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Among LAB, Lactiplantibacillus plantarum (formerly Lactobacillus plantarum) [48] is a versatile bacterium characterized by a high adaptability to many different conditions, being isolated from various ecological niches including dairy, fruits, cereal crops, vegetables, fish and fresh meat [49]. In addition, its presence in honeybee gut has been documented by several researchers [50][51][52], and its role, along with other bacteria and yeasts, in the transformation of fresh pollen into bee bread is well known [53,54]. L. plantarum pro-technological properties are exploited in different agri-food sectors [55][56][57][58][59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…It has been isolated in many different environmental niches, such as fruit, vegetables, all types of fermented foods, meat and fish [ 31 , 32 , 33 ]. L. plantarum strains have also been isolated from different honeybee species [ 34 , 35 , 36 , 37 ]. Several authors have demonstrated that L. plantarum colonizes the adult Drosophila melanogaster gut and that it influences different aspects of the insect’s development and life, exerting a growth-promoting effect on larvae under nutrient scarcity [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have proved that L. plantarum has a broad capacity to inhibit the growth of different pathogens, and different strains exert inhibitory activity towards bacteria and fungi. In addition, chemically different compounds with antibacterial and antifungal activity have been characterized in culture filtrates [ 43 , 44 , 45 , 46 ], L. plantarum also exhibits antagonist activity against Paenibacillus larvae , the causative agent of the quarantine disease American foulbrood, which affects A. mellifera larvae and pupae [ 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Over the years, several studies have obtained relevant data supporting the probiotic properties of L. plantarum [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%